Impact of high-risk investments on the maintenance of business competitiveness index in economic recovery - Argota Pérez, Yadira (2025)
The objective of the study was to determine the impact of high-risk investments on maintaining the business competitiveness coefficient in economic recovery. With a quantitative and descriptive approach, validated surveys (Cronbach's α) and 3CA and CAPROR software were used to analyze competitiveness and economic recovery, as well as a formula for the Risk and Bankruptcy Prediction Index. The results showed a Cronbach's alpha reliability of 0.71, ensuring internal consistency. AMTAWI exhibited a competitiveness coefficient of 1.2 in 2023 and projected 1.4 for 2024; ACINOX increased from 1.4 to 1.6, achieving excellence levels, while Imprenta Campos maintained a coefficient of 0.9. The Risk Index indicated low risk for AMTAWI (0.012), medium risk for Imprenta Campos (0.014), and high risk for ACINOX (0.021). Investments represented 65% of profitability in AMTAWI, 91% in ACINOX, and 33% in Imprenta Campos, with economic recoveries of 47%, 3%, and 26%, respectively. Investment and adaptation strategies proved key to stability and economic recovery. AMTAWI and ACINOX advanced towards excellence, while Imprenta Campos remained stable, highlighting the importance of balancing risks and maintaining prudence. It is concluded that competitiveness and business risk are dynamic, influenced by internal and external factors, with business adaptability being essential in the face of uncertainties.